2018
DOI: 10.7554/elife.29939
|View full text |Cite
|
Sign up to set email alerts
|

aPKC-mediated displacement and actomyosin-mediated retention polarize Miranda in Drosophila neuroblasts

Abstract: Cell fate assignment in the nervous system of vertebrates and invertebrates often hinges on the unequal distribution of molecules during progenitor cell division. We address asymmetric fate determinant localization in the developing Drosophila nervous system, specifically the control of the polarized distribution of the cell fate adapter protein Miranda. We reveal a stepwise polarization of Miranda in larval neuroblasts and find that Miranda's dynamics and cortical association are differently regulated between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 70 publications
4
47
0
Order By: Relevance
“… 55 for a review). Septins 56 , Cindr, Roughest 39 and Flare 37 can be linked in one way or another to the regulation of actomyosin, and at least the maintenance of Baz localization in mitotic NBs is also actin-dependent 57 . Intracellular long-range control of polarization has been further observed in eight-cell stage mouse blastomeres, where cell–cell contacts induce apical polarization at the opposite end of the cell 58 .…”
Section: Discussionmentioning
confidence: 99%
“… 55 for a review). Septins 56 , Cindr, Roughest 39 and Flare 37 can be linked in one way or another to the regulation of actomyosin, and at least the maintenance of Baz localization in mitotic NBs is also actin-dependent 57 . Intracellular long-range control of polarization has been further observed in eight-cell stage mouse blastomeres, where cell–cell contacts induce apical polarization at the opposite end of the cell 58 .…”
Section: Discussionmentioning
confidence: 99%
“…A shared characteristic of numerous polarity-related proteins, these domains are often the direct targets of regulatory kinases, allowing membrane association to be regulated in time and space. Miranda, Numb, Lgl and PAR-2 membrane binding domains are direct targets of the polarity-related kinase aPKC, providing a mechanism for exclusion from aPKC-enriched domains [32,34,36,37].…”
Section: Local Retentionmentioning
confidence: 99%
“…For instance, aPKC phosphorylation could induce conformation changes or protein interactions that hinder the polybasic domain from binding to PM. In addition, a recent study showed that although aPKC phosphorylation of the polybasic domain clears Mir from PM at interphase in asymmetrically dividing neuroblasts, at metaphase phosphorylation of the polybasic domain may actually enhance the actomyosin-dependent anchoring of Mir to basal PM 41 .…”
Section: Phosphorylation Targets Of Apkc In Cell Polaritymentioning
confidence: 99%